Genetic interrelationships of Spirometra erinaceieuropaei (Cestoda: Diphyllobothriidea), the causative agent of sparganosis in Europe - Čisovská Bazsalovicsová, Eva; Radačovská, Alžbeta; Lavikainen, Antti; Kuchta, Roman; Králová-Hromadová, Ivica (Parasite (Paris, France), 2022)
The geographic distribution of Spirometra erinaceieuropaei (Cestoda: Diphyllobothriidea), the causative agent of food/water-borne sparganosis, is restricted to Europe, where infected canids, felids, mustelids, suids, and reptiles have been documented from Poland, Ukraine, Belarus, Russia, Serbia, Estonia, Latvia, and Finland. The main objective of the current study was to map the molecular divergence of S. erinaceieuropaei from Finland using the complete sequences of the mitochondrial cytochrome c oxidase subunit 1 gene (cox1 mtDNA). Seven cox1 haplotypes were determined in 15 tapeworms from Eurasian lynx (Lynx lynx) from three localities in southern Finland. In addition, the first inter-population study of S. erinaceieuropaei based on currently obtained data on cox1 from Finland and previously published data from Finland, Latvia, Ukraine, and Poland, was performed. The haplotype network showed a star-like pattern without specific subdivision of lineages according to the locality. Samples from Finland, Latvia, and Poland shared several haplotypes and formed the common Baltic lineage. The haplotype of S. erinaceieuropaei from Ukraine was unique and placed on a separate mutational pathway, suggesting a different lineage of the parasite.
Keywords: cox1 haplotypes; Food/water-borne zoonosis; Molecular genotyping; Spirometra; DNA, Mitochondrial; Genetic lineages; Sparganosis; Sparganosis in Finland; Animals; sparganóza; Phylogeny; zvířata; fylogeneze; mitochondriální DNA; Europe; Evropa